2009
DOI: 10.1159/000224790
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dual Blockade of the Renin-Angiotensin System on Thirst in Hemodialysis Patients

Abstract: Background/Aims: Angiotensin II promotes sodium retention and influences the central regulation of fluid intake. Clinical studies on the effect of an angiotensin-converting enzyme inhibitor (ACEI) on xerostomia and thirst in chronic hemodialysis (HD) patients were scarce and gave contradictory results. We hypothesized that a more effective inhibition of the renin-angiotensin-aldosterone axis with the combined ACEI and angiotensin receptor antagonist administration may reduce thirst and xerostomia,thereby decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
(50 reference statements)
0
20
0
Order By: Relevance
“…We also observed no correlation between thirst, xerostomia, IDWG, or salivary flow rate and the use of ACEI or ARB. One recent study also found chronic ACEI therapy was not effective in reducing thirst and IDWG [31,32]. We found significant relationships among thirst, xerostomia and IDWG, suggesting that xerostomia and thirst might be one of the reasons that lead to higher fluid intake.…”
Section: Discussionmentioning
confidence: 42%
“…We also observed no correlation between thirst, xerostomia, IDWG, or salivary flow rate and the use of ACEI or ARB. One recent study also found chronic ACEI therapy was not effective in reducing thirst and IDWG [31,32]. We found significant relationships among thirst, xerostomia and IDWG, suggesting that xerostomia and thirst might be one of the reasons that lead to higher fluid intake.…”
Section: Discussionmentioning
confidence: 42%
“…Thirst is a common complaint for patients with congestive heart failure (43,44), frequently plagues dialysis patients, and likely contributes to the prevalence of hyponatremia in these populations. Pharmacologic blockade of the renin-angiotensin axis, although theoretically attractive, does not seem to reduce thirst (45). In addition to disorders of fluid volume, thirst is also frequently encountered in patients with psychiatric disorders, reported in up to 25% of hospitalized patients with schizophrenia.…”
Section: Thirstmentioning
confidence: 99%
“…74 The hypothesis that an effective inhibition of the reninangiotensin-aldosterone axis with the combined ACE inhibitors and angiotensin receptor antagonist administration may reduce thirst and xerostomia, [75][76][77][78] thereby decreasing IDWG, has not been confirmed in a recent double-blind crossover study. 79 Conclusion It is still difficult to limit IDWG in patients on chronic hemodialysis. The therapeutic strategies used so far have shown to be of limited efficacy in terms of size and duration.…”
Section: Other Treatmentsmentioning
confidence: 99%